2014
DOI: 10.3892/etm.2014.1501
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of senegenin on splenectomy-induced postoperative cognitive dysfunction in elderly rats

Abstract: Postoperative cognitive dysfunction (POCD) is common in elderly patients. Senegenin, an active component of extracts from Polygala tenuifolia root, a traditional Chinese medicine, has neuroprotective and neuroregenerative effects. However, the mechanism underlying the effects of senegenin against postoperative cognitive impairment in elderly individuals has yet to be elucidated. The aim of this study was to investigate the protective effects of senegenin on the cognitive functions of elderly rats with splenect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 22 publications
5
24
0
Order By: Relevance
“…Various animal models of POCD have demonstrated elevations in pro-inflammatory cytokines and other proinflammatory mediators in the hippocampus (Cibelli et al, 2010; Barrientos et al, 2012; Terrando et al, 2013; Hovens et al, 2014a,b; Zhang et al, 2014). We, and others, have shown that hippocampal memory function was significantly more impaired by surgery in aged animals compared to younger control animals (Barrientos et al, 2012; Hovens et al, 2013, 2014b; Li et al, 2014; Sun et al, 2014; Yu et al, 2014). This pattern has been found following a variety of surgical procedures including exploratory abdominal surgery (Barrientos et al, 2012; Hovens et al, 2014b; Li et al, 2014), stabilized tibial fracture surgery (Sun et al, 2014), and partial hepatectomy (Li et al, 2013).…”
Section: Introductionmentioning
confidence: 58%
“…Various animal models of POCD have demonstrated elevations in pro-inflammatory cytokines and other proinflammatory mediators in the hippocampus (Cibelli et al, 2010; Barrientos et al, 2012; Terrando et al, 2013; Hovens et al, 2014a,b; Zhang et al, 2014). We, and others, have shown that hippocampal memory function was significantly more impaired by surgery in aged animals compared to younger control animals (Barrientos et al, 2012; Hovens et al, 2013, 2014b; Li et al, 2014; Sun et al, 2014; Yu et al, 2014). This pattern has been found following a variety of surgical procedures including exploratory abdominal surgery (Barrientos et al, 2012; Hovens et al, 2014b; Li et al, 2014), stabilized tibial fracture surgery (Sun et al, 2014), and partial hepatectomy (Li et al, 2013).…”
Section: Introductionmentioning
confidence: 58%
“…Yang et al compared the roles of propofol and isoflurane in the neurodegeneration and cognitive impairment in neonatal mice, and found that both caused significant apoptosis in the developing brain, with isoflurane being more potent (17). In addition, isoflurane significantly increased the levels of the plasma neurodegenerative biomarker, S100β (18). Neuroinflammation has been demonstrated to be a key factor for the progression of cognitive dysfunction after surgery and/or anesthesia (19).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation has been demonstrated to be a key factor for the progression of cognitive dysfunction after surgery and/or anesthesia (19). During the development of POCD, the expression levels of various proinflammatory cytokines has been reported to be significantly increased, including TNF-α, IL-1β, IL-6 and IL-8 (18). For example, Yu et al (18) showed that splenectomy induced a transient cognitive deficiency in elderly rats, accompanied by notable upregulation of TNF-α, IL-1β, IL-6 and IL-8 expression in the in the hippocampal tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases of POD, levels of pro-inflammatory cytokines are also significantly increased in hippocampus following peripheral surgical procedures [30,138,141,142145]. Animal studies identifying the effects of surgical procedures have confirmed that deficits in learning and memory are associated with elevated levels of pro-inflammatory cytokines in hippocampus compared to young animals [138,144,146149]. Biological and physiological mechanisms of the neuroinflammatory components underlying cognitive decline associated with POD and AD are unknown, however the role of pro-inflammatory cytokines in hippocampal function may provide an overlapping mechanism by which cognitive decline occurs in cases of POD that may manifest into AD.…”
Section: Cognition and Neuroinflammationmentioning
confidence: 99%